Can synergy in Triple Helix relations be quantified? A review of the development of the Triple Helix indicator - Loet Leydesdorff; Han Woo Park (Triple Helix, 2014)
Triple Helix arrangements of bi- and trilateral relations can be considered as adaptive ecosystems. During the last decade, we have further developed a Triple Helix indicator of synergy as reduction of uncertainty in niches that can be shaped among three or more sets of relations. Reduction of uncertainty can be generated in correlations among distributions of relations, but this (next-order) effect can be considered as a feedback counterbalancing the uncertainty generated in the localized relations. We first explain the indicator and then review possible results when this indicator is applied to (i) co-author networks of academic, industrial, and governmental authors and (ii) synergies in the distributions of firms over geographical addresses, technological classes, and industrial-size classes for a number of nations. Co-variation is then considered as a measure of relationship. The balance between globalizing and localizing dynamics can be quantified. Too much synergy locally can also be considered as lock-in. Tendencies are different for the globalizing knowledge dynamics versus locally retaining wealth from knowledge in industrial innovations.
Keywords: 330; Indicator; Niche; Probabilistic entropy; Synergy